ROBUST M-ESTIMATORS' Parameter Scale is Highly Efficient on Base Q Grades - Zahraa Khaled Gaafar; Anwer Fawzi Ali (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Russiva and Crookes proposed the widely used, highly efficient, robust Q-score parameter scale in their 1993 work, and they approximated it using